PENGAWASAN PEMASANGAN PAPAN REKLAME DI KECAMATAN TAMPAN KOTA PEKANBARU - Nur Astika; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Supervision Installation of billboard in Kecamatan Tampan Pekanbaru City conducted by (Satpol PP) is a government agency responsible for the Supervision of Board Installation and according to city regulation Pekanbaru Number 4 Year 2011 About Reklame and mayor regulation Pekanbaru Number 24 Year 2013 About Implementation of Advertising. The purpose of this study is to find out how the implementation of Monitoring Board Installation in Kecamatan Tampan Pekanbaru City. Theoretical concepts used by the researcher are the indicators that influence the supervision used by Brantas where the indicator used is to determine the standard to be used, measure the implementation or the results achieved, compare the implementation or results with the standard and determine the deviation if there is and take action improvement if there are deviations. This research uses qualitative descriptive method, using interview technique, observation and documentation. The results of this study indicate that (Satpol PP) in this case as an authority in supervising the installation of billboards has not done the supervision of the installation of billboards maximally and there are still many deficiencies in terms of monitoring the installation of billboards such as the number of billboards that have expired time still attached and limited human resources so that the need for additional personnel in the supervision team so supervision runs optimally. Keywords: supervision, advertisement installation, organizing